The Influence of Price and Service Quality on the Purchase Decision - Erpurini, Wala; Irawan, Noval Indra; Nurlaela, Widiya; Pratiwi, Arny Resmi Herliani (Almana : Jurnal Manajemen dan Bisnis, 2023)
The background to this research is that there is a phenomenon that the variable service quality at Holland Bakery Lembang is not good enough. Apart from that, the influence of price is a supporting factor in determining purchasing decisions at Holland Bakery. This study aims to understand the influence received from price and service quality on purchasing decisions at Holland Bakery Lembang, West Bandung Regency. both partially and as a whole. This study was conducted using quantitative research methods with descriptive and associative approaches. The research results stated that the influence of price on purchasing decisions was partially shown at 7.4%. influence of service quality on partial purchasing decisions shown by 64.2%. coefficient of determination R square of 0.716. With this coefficient value, it can be concluded that the independent variables in this study, namely price and service quality, have an influence of 71.6% on purchasing decisions and the remaining 28.4% is influenced by other factors not included in this study.